Food Science and Technology / Fourth Edition - Hawthorn John; John Murray; Parducci Lelio; Pyke Magnus (1982)
This book provides a concise introduction to the subject: it covers the basic principles of chemistry, physics and biology, which underlie both the most traditional and the most modern methods of food processing. Scientific Principles Applied to Food, Modern Conceptions of Chemistry and Physics and Biology, Traditional Methods of Processing Food and Their Scientific Significance, Practical Technology, Cereal Chemistry and Technology, Wheat, Rice, Barley, Oats, Maize, Meat and Fish and Poultry, Fish, Milk and Cheese and Eggs, Fats and Oils, Vegetable Oils, Butter, Margarine, Hydrogenation of Oils, Rancidity, Sugar and Syrup and Soft Drinks, Fruit and Vegetables, Fruit, General Principles of Technology, Vegetables, Green Vegetables, Sweet Potatoes, Some Modern Technological Processes, Canning, Quick Freezing, Dehydration, The Training and Employment of Food Technologists, The Present Scope of Food Science and Technology, Food Technology and the Next Twenty Years, Appendices, Index.